The Effect of Awareness Toward Dementia on Dementia Education Program of Adolescents (Medico Legal Update, 2019)
Background/Objectives: As the elderly population increases, dementia patients are rapidly increasing as well and dementia causes various social problems such as burden and cost of care. These social problems will be affected by the present adolescents who will become responsible for dementia patients and aged generation. The purpose of this study was to survey the effect of awareness toward dementia on Dementia Education Program(DEP) of adolescents. Throughout the program, 32 subjects were educated and received tasks related to dementia.Method/Statistical Analysis: Subjects were recruited online and DEP was processed for 2 days with 9 educational topics. By providing volunteer work hours accepted in high school when the tasks were completed, we increased the participation. To evaluation the awareness toward dementia, we used the dementia awareness questionnaire used on nationwide study on the prevalence of dementia in Korean elders by the Ministry of Health and Welfare. To analyze the subject’s general characteristics, descriptive analysis was used. Conducted paired T-test to analyze the change of awareness toward dementia before and after DEP in the group.Findings: Dementia awareness questionnaire’s perfect score is 15. Higher the score is, greater the awareness toward dementia. Before DEP, the score was. After DEP, the score was. Comparing the before and after scores, the score increased. The result showed statistical significant difference.Improvements/Applications: The study showed that the effect of awareness toward dementia on DEP of adolescents was positive. This result can be used as a background data announcing the need for early education through school health education, starting from the present adolescence that will directly support the elderly generation in future.